PERANCANGAN SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA PAUD ASSIBYAN SERANG BANTEN - Jeva Afriliano (2022)
Until now, there are still many schools whose academic processing is still done manually, namely by taking notes using paper. This causes the information to be conveyed will experience delays due to inefficient performance, the result is that the data processing is still at risk of being invalid. Moreover, the paper used for data processing can be at risk of being damaged or lost. The purpose of this research is to design a web-based academic information system to facilitate data processing and information delivery in PAUD Assibyan using the Waterfall method using the PHP Native language and using the MVC concept and the database server using MySQL. With this web-based academic information system, it is easier for schools to process data more effectively and efficiently and make it easier for parents to get information related to their child's development.